(untitled) (Journal of Parents and Teachers, 2014)
The family-school binomial is a fundamental and indisputable educational principle; however, this relationship can sometimes be anarchic and based on particular criteria. It is therefore essential that parents receive training in order to participate actively and fully. If the family-school binomial works properly, a coherent and structured development of the pupil will be achieved.